Alpha power decreases associated with prediction in written and spoken sentence comprehension. (13th August 2022) - León-Cabrera, Patricia; Piai, Vitória; Morís, Joaquín; Rodríguez-Fornells, Antoni
Abstract: Alpha and beta power decreases have been associated with prediction in a variety of cognitive domains. Recent studies in sentence comprehension have also reported alpha and/or beta power decreases preceding contextually predictable words, albeit with remarkable spatiotemporal variability across reports. To contribute to the understanding of the mechanisms underlying this phenomenon, and the sources of variability, the present study explored to what extent these prediction-related alpha and beta power decreases might be common across different modalities of comprehension. To address this, we re-analysed the data of two EEG experiments that employed the same materials in written and in spoken comprehension. Sentence contexts were weakly or strongly constraining about a sentence-final word, which was presented after a 1 s delay, either matching or mismatching the expectation. In written comprehension, alpha power (8–12 Hz) decreased before final words appearing in strongly (relative to weakly) constraining contexts, in line with previous reports. Furthermore, a similar oscillatory phenomenon was evidenced in spoken comprehension, although with relevant spatiotemporal differences. Altogether, the findings agree with the involvement of both modality-specific and general-domain mechanisms in the elicitation of prediction-related alpha power decreases in sentence comprehension. Specifically, we propose that this phenomenon might partly reflect richer and more precise information representation when linguistic contexts afford prediction.